Factors influencing students’ happiness, vitality, and self-esteem - Majauskiene, Daiva; Istomina, Natalja; Valanciene, Dovile; Dadeliene, Ruta; Sidlauskiene, Aurelija; Aukstikalnis, Tomas; Jamontaite, Ieva Egle; Strazdaite, Emilija; Zilinskiene, Ramune; Gintiliene, Milda; Sarkauskiene, Asta; Skurvydas, Albertas (Frontiers in Psychology, 2024)
The happiness and well-being of individuals are among the most important components of life. However, there remains a lack of evidence regarding the relationships between students' happiness, vigor, and self-esteem on the one hand and various complex factors on the other hand. We conducted a cross-sectional study involving 397 students from various Lithuanian universities. We determined students' happiness, self-esteem, vigor, healthy lifestyles, perceived stress, personality traits, academic achievements and motivation by using validated scales. The study indicates that while happiness and self-esteem are not linked to healthy lifestyles, vigor is positively associated with moderate-to-vigorous physical activity (MVPA) and healthy eating, and negatively with body mass index (BMI). Happiness and vigor inversely relate to stress, and happiness and self-esteem inversely relate to depression. Vigor is positively related to extraversion, and self-esteem to neuroticism. Happiness, vigor, and self-esteem are not linked to academic achievements, but happiness relates to non-utilitarian decisions, and selfesteem to emotional intelligence and non-utilitarian decisions. Happiness, vigor, self-esteem were not linked to intrinsic motivation to study, but self-esteem was inversely related to amotivation and childhood violence. This study fills the research gap and deepens the understanding of what determines students' happiness and vigor, and self-esteem.